Presence of an Arterial Feeding Vessel on Cross-Sectional Imaging Predicts Treatment Response and Survival after Transarterial Chemoembolization for Unresectable Hepatocellular Carcinoma: A Retrospective Multivariable Analysis of 138 Patients - Guan, Justin J.; Laroia, Sandeep T.; McBride, Aaron F.; Sun, Shiliang; Huang, Lihong; Yang, Jingzhen; Dunlay, Michael; Nagpal, Prashant (Digestive Disease Interventions, 2023)
Finding a feeding vessel with diameter greater than 0.9 mm during transarterial chemoembolization (TACE) for hepatocellular cancer (HCC) has been shown to predict tumor necrosis on subsequent pathology. However, whether this translates into a useful clinical predictor for post-chemoembolization response and survival is unknown. This study aimed to determine whether the presence of an arterial feeder on pre-TACE cross-sectional imaging is associated with treatment response and survival after TACE for unresectable HCC. Retrospective medical record search for all chemo-embolizations performed for HCC from 2015 to 2016 yielded 138 patients who underwent 275 TACE sessions spanning 2011 to 2017. Patients consisted of 98 males (71%) with mean age of 62 (range, 37–86). Each patient underwent an average of two TACE sessions (range, 1–11). Endpoints included target tumor response and overall response defined by the mRECIST criteria, as well as patient survival. Preprocedural MRI/CT was reviewed for the presence of arterial feeder. Multivariable logistic regressions and Cox proportional hazard regressions were used to assess the effects of arterial feeder presence on treatment response and survival, respectively, adjusting for other covariates. Overall response was seen in 69% of patients. Arterial feeder was present on preprocedural cross-sectional imaging for 28% of TACE sessions. Median survival was 26.5 months (interquartile range, 13.2–38.1). The presence of arterial feeder led to better target tumor response (OR = 11.9, p < 0.0001), overall response (OR = 9.3, p < 0.0001), and improved survival (HR = 0.55, p = 0.02). The presence of an arterial feeder on pre-TACE cross-sectional imaging is associated with target tumor response, overall response, and survival after TACE.
Keywords: hepatocellular cancer; TACE; chemoembolization